Long term prognosis of out-of-hospital cardiac arrest due to idiopathic ventricular fibrillation - a tertiary center experience. (24th May 2021) - Alves Pinto, R; Proenca, T; Martins Carvalho, M; Grilo, PD; Resende, CX; Torres, S; Calvao, J; Amador, AF; Costa, C; Oliveira, S; Pestana, G; Mota Garcia, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background:  Sudden cardiac death (SCD) is an uncommon event in the absence of structural heart disease. However, ventricular fibrillation (VF) may occur in patients with unknown cardiac disease and a comprehensive work-up is needed to further improve diagnostic. Still, a significant and heterogenous group of patients remains labelled of Idiopathic VF and limited data is available regarding their natural history. Purpose: The aim of this study was to evaluate the clinical outcomes of survivors of an aborted sudden cardiac death due to idiopathic VF or pulseless ventricular tachycardia (VT) and to assess possible predictors of recurrence. Methods:  Patients who survived an idiopathic VF or pulseless VT between 2005 and 2019 referred to a cardiac defibrillator (ICD) implantation were included. Patients were followed for 1 to 15 years (median follow-up of 7 years). Clinical and device data were collected. Results: A population of 29 patients, 59% male, with a median age of 50 years (age ranging from 18 to 76) at the time of the aborted SCD was studied. All patients implanted an ICD (69% single chamber, 24% dual chamber and 3% subcutaneous) at the index hospitalization. The initial rhythm was VF in 76% and pulseless VT in 24%. In relation to the context of the arrhythmic event, 48.3% occurred during daily life activities, 13.8% after an emotional stress, 6.9% during efforts and a similar percentage occurred either in rest or asleep. Of note, 12.5% of patients had previous history of syncope. Normal ECG was present in 83% of patients. Family history of SCD was present in 12% of the cases. As for the cardiovascular risk factors, 61.5% had hypertension, 19% dyslipidemia, 17% diabetes, 31% were smokers or previous smokers. Paroxysmal atrial fibrillation was present in 15% of patients. To exclude possible causes of VF, all patients were submitted to coronary angiogram and echocardiogram, 64% to genetic testing, 68% to cardiac magnetic resonance, 20% to electrophysiologic study, 12% to pharmacological provocative test and 4% were submitted to endomyocardial biopsy. At follow-up, an etiological diagnosis was established in 31% of patients: 3 events were attributed to coronary vasospasm, 3 to short coupled polymorphic VT, 1 patient had long QT syndrome, 1 had Brugada syndrome and in 1 patient an ANK2 mutation was identified. As for the clinical outcomes, 8% patients died (from non-arrhythmic causes), 31% patients received appropriate therapies and 19% had unappropriated shocks (of those 60% for sinus tachycardia and 40% for supraventricular tachycardia). Conclusion: Etiologic diagnosis and prediction of recurrence of arrhythmic events in patients with idiopathic VF is challenging, even with a long-term follow-up and more sophisticated diagnostic evaluation.  Idiopathic VF is a rare but serious condition with recurrence in about one third of patients. Although not free of complications, ICD remains the gold standard of treatment.